Fiscal sustainability: Must the problem be diminished before we can see it? - Erling Holmøy (Statistics Norway, Research Department, 2007)
Assessments of fiscal sustainability (FS) problems should be based on present values of government revenues and expenditures over an infinite horizon. The paper shows that realistic assumptions imply that the growth rate of government expenditure components may exceed both the steady state growth rate of the economy and the relevant discount rate, which makes the FS problem immeasurably large. The common practice of ad hoc exogenous alignment of government expenditures to the steady state growth path after some distant year may significantly diminish the FS problem, since the effective discounting is likely to remain low. Low effective discounting also makes the FS assessment highly non-robust, reducing its political relevance. It suggests that the fiscal sustainability should be improved by reducing the growth rates of government expenditures, a strategy followed in e.g. the Swedish pension reform.
Keywords: H30; H55; H62; 330; Fiscal sustainability; long run projections; discounting